Needs Analysis and Teachers’ Perceptions: A Study of English Undergraduate Students - Abdul Qadar (University of Chitral Journal of Linguistics and Literature)
Needs Analysis in the context of language-learning-teaching is an important process to design a certain course and syllabus. It helps course designers to set objectives, choose content, method of instruction, appropriate teaching aids and classroom activities for different courses. This paper reports the perceptions of the researchers on the English language learning needs of the English undergraduate students of Shaheed Benazir Bhutto University Sheringal, Pakistan. The data is based on the researchers’ personal experience and a first-hand observation of the population as the researchers have been teaching in the target context for about a decade. Furthermore, the researchers have always been in discussion with their students and colleagues about the target students’ English leaning needs, preferred learning styles, motivation in learning English, interest, strengths/weaknesses, and attitude toward English learning in the target setting. Learners’ assignments, exam answer sheets, and presentations have also been used is a source of data collection. A needs analysis model proposed by Hutchinson and Waters (1987) has been applied in order to analyze the data. The results show that the students lack well grammatical sentences, have poor spellings, capitalization problems, limited vocabulary, unaware of collocations, poor/slow reading comprehension, and lack of effective presentation skills. Furthermore, most of the students have lack of involvement in classroom activities and feel shy in speaking English language. It was reported that provision of authentic material, interesting activities, suitable audio-visual aids, relevant texts, language labs and other logistic arrangements can better help them in learning English language. The findings demonstrate that the students wished to have a learner-centered-course which helps them excel in their academic life and learning English language.